Listening to food workers: Factors that impact proper health and hygiene practice in food service - Clayton, Megan L. (Int J Occup Environ Health, 2015)
BACKGROUND: Foodborne disease is a significant problem worldwide. Research exploring sources of outbreaks indicates a pronounced role for food workers' improper health and hygiene practice. OBJECTIVE: To investigate food workers' perceptions of factors that impact proper food safety practice. METHOD: Interviews with food service workers in Baltimore, MD, USA discussing food safety practices and factors that impact implementation in the workplace. A social ecological model organizes multiple levels of influence on health and hygiene behavior. RESULTS: Issues raised by interviewees include factors across the five levels of the social ecological model, and confirm findings from previous work. Interviews also reveal many factors not highlighted in prior work, including issues with food service policies and procedures, working conditions (e.g., pay and benefits), community resources, and state and federal policies. CONCLUSION: Food safety interventions should adopt an ecological orientation that accounts for factors at multiple levels, including workers' social and structural context, that impact food safety practice.